Consensus definition of a radiologically healed fistula on magnetic resonance imaging in perianal Crohn’s disease: an international Delphi study - Ailsa L Hart; Phillip Lung; Phil Tozer; Jalpa Devi; Jaap Stoker; David H Ballard; Shivani Joshi; Michelle Doering; Easan Anand; Anna Antoniou; Parakkal Deepak (BMJ Open)
Introduction Perianal fistulising Crohn’s disease (pfCD) is a distinct and debilitating phenotype seen in around one-third of patients with CD. Clinical trials in pfCD are increasingly using magnetic resonance imaging (MRI) criteria as a primary endpoint, but there is heterogeneity in the radiological definition of a healed perianal fistula that currently limits our ability to perform meaningful meta-analyses of studies. Our aim is to standardise outcomes through the generation of an international consensus definition of a radiologically healed fistula.Methods and analysis This international Delphi consensus study employs a two-part strategy.The first is a systematic review to identify a longlist of variables used to define radiological healing in pfCD. MRI-based indices used to score fistula severity and healing will be assessed for their methodological quality using Consensus-based Standards for the selection of health Measurement Instruments (COSMIN). The systematic review protocol will be conducted using COSMIN methodology and reported using Preferred Reporting Items for Systematic Reviews and Meta-Analyses.The second part will be an online Delphi consensus, guided by the results of the systematic review. Radiologists, gastroenterologists and colorectal surgeons with expertise in the management of pfCD will be invited to take part in two to three rounds of online surveys. Once an a priori threshold of >80% agreement is reached on individual radiological components used to define ‘healing’ and ‘healed’, a final meeting of key stakeholders will be organised to generate a consensus definition of a healed fistula.Ethics and dissemination The study has been deemed exempt from a formal Research Ethics Committee review as no patients will participate directly in the consensus process, given the technical nature of the research question. The study is registered with the local R&D department (Reference RD24/007). Publication of this study will help standardise radiological endpoint measurement in clinical trials of pfCD and improve the synthesis and meta-analysis of comparative studies.PROSPERO registration number CRD42024504334.